+0  
 
+1
247
2
avatar+701 

needed 

 Oct 10, 2018
 #1
avatar+6115 
+3

If the expression (x-a) is a factor of f(x), then f(a) = 0.

 

So just plug each of them into f(x)

 

f(5) = 160

 

f(-3) = 0

 

f(15) = 4320

 Oct 10, 2018
 #2
avatar+107493 
+2

x^3 + 5x^2 - 9x  - 45

 

We can factor this by grouping

 

x^2 (x + 5)  - 9 ( x + 5)       [ ( x + 5) is the common factor] 

 

(x + 5) ( x^2 - 9 )

 

(x + 5) ( x + 3) ( x - 3)

 

So....only  ( x + 3)  is a factor

 

 

cool cool cool

 Oct 10, 2018

29 Online Users